1979
DOI: 10.1007/bf01007111
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of hypertonicity in muscles of lip retraction

Abstract: An EMG biofeedback program was developed for a 56-year-old Parkinsonism patient who exhibited pathological lip hypertonia and retraction. The program was designed to achieve the following goals: (1) to demonstrate a reduction in postural lip hypertonicity and (2) to demonstrate a reduction in lip hypertonicity during a series of increasingly complex speech activities. To achieve the first goal, contrastive tasks of full contraction and relaxation were utilized. Each posture was sustained while voltage measurem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

1982
1982
2008
2008

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 4 publications
0
8
0
Order By: Relevance
“…For individuals with SCP, sEMG has the potential to reduce muscle spasticity by facilitating muscle control using relaxation. Relaxation reduces muscle tone and facilitates improved range of orofacial movement and muscle functioning, which ultimately improves articulation and speech performance [14][15][16][17][18]. More studies investigating sEMG biofeedback for treating articulatory disorders are required to confirm these findings in children with SCP.…”
Section: Introductionmentioning
confidence: 75%
See 2 more Smart Citations
“…For individuals with SCP, sEMG has the potential to reduce muscle spasticity by facilitating muscle control using relaxation. Relaxation reduces muscle tone and facilitates improved range of orofacial movement and muscle functioning, which ultimately improves articulation and speech performance [14][15][16][17][18]. More studies investigating sEMG biofeedback for treating articulatory disorders are required to confirm these findings in children with SCP.…”
Section: Introductionmentioning
confidence: 75%
“…The findings suggest that sEMG intervention facilitates a reduction in orofacial spasticity and may be an effective treatment modality for children with CP. In adults, several case studies have reported improved articulation and overall intelligibility following sEMG biofeedback treatment with severe spastic dysarthria [14][15][16][17][18].…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…As for speech and language therapy, biofeedback has been used in several disorders: Hearing disorders and deafness (Stark, 1971), resonance disorders (Brunner et al, 1994;Fletcher, 1972;Garber, Burzynski, Vale, & Nelson, 1979;Goldstein, Ziegler, Vogel, & Hoole, 1994;Künzel, 1982;Moller, Path, Werth, & Christiansen, 1973;Shelton, Paesani, McClelland, & Bradfield, 1975;Whitehill, Stokes, & Man, 1996), neurogenic speech disorders including facial paralysis (Daniel & Guitar, 1978;Finley, Niman, Standley, & Wansley, 1977;Gentil, Aucouturier, Delong, & Sambuis, 1994;Goldstein et al, 1994;Hammerschlag, Brudny, Cusumano, & Cohen, 1987;Hand, Burns, & Ireland, 1979;Jankel, 1978;Nemec & Cohen, 1984;Netsell & Cleeland, 1973;Netsell & Daniel, 1979;Rubow, Rosenbek, Collins, & Celesia, 1984;Rubow & Swift, 1985;Schram & Burres, 1984), fluency disorders (Craig & Cleary, 1982;Guitar, 1975;Hanna, Wilfling, & McNeill, 1975), articulation disorders (Brooks, Fallside, Gulian, & Hinds, 1981;Michi, Yamashita, Imai, Suzuki, & Yoshida, 1993), swallowing disorders (Denk & Kaider, 1997;Huckabee & Pelletier, 1999) and respiratory disorders (Murdoch, Pitt, Theodoros, & Ward, 1999). Also in the field of voice disorders, there have been studies regarding the use and effects of biofeedback, as will be discussed in the next section.…”
Section: Introductionmentioning
confidence: 98%
“…The patient was presented with a tone whose frequency was analogous to the voltage recorded from the electrodes and she had to concentrate on lowering this tone. This method was replicated by Hand et al [7], who also used auditory feedback. Netsell and Daniel [8] used a multiple treatment ap proach to train a flaccid dysarthric patient to improve his speech: auditory biofeedback of lip EMG during nonspeech and speech activi ty and visual biofeedback of glottal flow dur ing sustained phonation of vowels.…”
Section: Treatment Of Dysarthrias Using Emg Biofeedback Technique: Ovmentioning
confidence: 94%